Blood pressure, brain lesions and cognitive decline in patients with atrial fibrillation - Carmine, Désirée; Aeschbacher, Stefanie; Coslovsky, Michael; Hennings, Elisa; Paladini, Rebecca E.; Peter, Raffaele; Burger, Melanie; Reichlin, Tobias; Rodondi, Nicolas; Müller, Andreas S.; Ammann, Peter; Conte, Giulio; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background The influence of atrial fibrillation (AF) and blood pressure (BP) on brain lesions and cognitive function is unclear. We aimed to investigate the association of BP with different types of brain lesions and cognitive decline in patients with AF. Methods Overall, 1,213 AF patients underwent standardized brain magnetic resonance imaging at baseline and after 2 years, as well as yearly neurocognitive testing. BP was measured at baseline and categorized according to guidelines. New lesions were defined as new or enlarged brain lesions after 2 years. We defined cognitive decline using three different neurocognitive tests. Logistic and Cox regression analyses were performed to examine the associations of BP with new brain lesions and cognitive decline. Results The mean age was 71 ± 8.4 years, 74% were male and mean BP was 135 ± 18/79 ± 12 mmHg. New ischemic lesions and white matter lesions were found in 5.4% and 18.4%, respectively. After multivariable adjustment, BP was not associated with the presence of new brain lesions after 2 years. There was no association between BP and cognitive decline over a median follow-up of 6 years when using the Montreal Cognitive Assessment or Digit Symbol Substitution Test. However, BP categories were inversely associated with cognitive decline using the Semantic Fluency Test, with the strongest association in patients with hypertension grade 1 [Hazard Ratio (95% Confidence Interval) 0.57(0.42 to 0.77)], compared to patients with optimal BP (p for linear trend: 0.025). Conclusions In a large cohort of AF patients, there was no association between BP and incidence of brain lesions after 2 years. Also, there was no consistent association between BP and cognitive decline over a follow-up of 6 years. Clinical Trial Registration https://clinicaltrials.gov/study/NCT02105844, Identifier (NCT02105844).